Alzheimer's Disease - A Comprehensive Review - Kinga Woźniak; Monika Gardian-Baj; Magdalena Jung; Patryk Hedesz; Maximilian Jung; Aleksandra Żuk-Łapan; Aleksandra Doryń; Krystian Jędral; Aleksandra Włodarczyk; Alicja Szczerbiak; Justyna Popczyńska (Journal of Education, Health and Sport, 2024)
Introduction: Alzheimer's disease (AD) remains a pervasive and challenging neurodegenerative disorder with profound implications for individuals, families, and societies. As the most prevalent cause of dementia globally, AD's prevalence is set to rise significantly in the context of an aging population. This introductory section emphasizes the urgent need for a comprehensive understanding of the disease, encompassing both its molecular intricacies and the socio-economic burden. With age being the primary risk factor, recent research has delved into the complex interplay of genetic predisposition and environmental influences, reshaping our understanding of AD from a multifactorial perspective.